Emotion as Document: Death and Dying in the Second World War Art of Jack Nichols - Brandon, Laura (Material Culture Review, 1998)
The paintings, drawings and watercolours of Canada’s Second World War art collection are a source of contemporary technical, social and cultural data. Some of the more than 5000 works in the collection also provide the evidence of the human emotions experienced in wartime, particularly when servicemen were brought face to face with terrible sights. This is a significant and hitherto unexplored aspect of the war art collection. This paper will explore the Canadian war art collections with particular reference to the work of naval artist Jack Nichols. Although Nichols’ work lacks detail and clarity, it provides the more truthful experience of wartime life at sea. Unlike many of Canada’s Second World War art works, Nichols’s works address death and its surrounding emotions. As such, his compositions are invaluable tools to expand our understanding of the naval servicemen’s experience. Résumé Les peintures, les croquis et les aquarelles de la collection du Canada sur la Seconde Guerre mondiale forment une véritable banque de données techniques, sociales et culturelles contemporaines. Une partie des 5 000 œuvres et plus constituant la collection laisse transparaître les sentiments que l’on peut éprouver en temps de guerre, notamment lorsqu’on se retrouve subitement devant une scène atroce. Il s’agit d’un aspect important, mais peu connu, de la collection d’œuvres sur la guerre. Cet article fait un survol des collections du Canada d’œuvres d’art sur la guerre, s’attardant aux travaux de l’artiste Jack Nichols, sur la marine au temps de la Seconde Guerre mondiale. Quoiqu ’ils manquent de précision et de netteté, ses tableaux évoquent avec le plus de véracité ce qu ’est la vie en mer par temps de guerre. À la différence de nombreuses œuvres canadiennes illustrant la Seconde Guerre mondiale, les œuvres de Nichols gravitent autour de la mort et des émotions qu ’elle provoque. Aussi, les créations de l’artiste constituent-elles des aides inestimables pour comprendre l’expérience vécue par les membres de la marine durant la guerre.